Effects of adding alloying elements to nickel on the hardening of WC–Ni cemented carbides - Jungi Seo; Jaemin Song; Doyeon Lee; Junyeol Yang; In-Hyeok Choi; Myungjae Kim; Hanjung Kwon (Journal of Asian Ceramic Societies)
In this study, we investigated the hardening effect on WC–(Ni, M) cemented carbides of adding alloying elements (M = Co, Cu, and W). First, the intrinsic properties of (Ni, M) alloys were predicted based on theoretical calculations. The solid-solution strengthening effect due to the addition of M to Ni and the phase changes in the WC–(Ni, M) cemented carbide were then confirmed experimentally. As regards the intrinsic properties, the Pugh’s constant of (Ni, Co) was the lowest (1.88), and it was predicted that (Ni, Co) would have the stiffest properties among the three types of nickel alloys. Because of the relatively larger lattice constant of Cu compared to that of Co, however, the strengthening effect of Cu is greater than that of Co, making the (Ni, Cu) alloy superior to the (Ni, Co) alloy in terms of yield strength. In the case of the (Ni, W) alloy, unlike that of the (Ni, Co) and (Ni, Cu) alloys, W precipitation occurred because of the low affinity between Ni and W. Owing to the large lattice strain effect in the Ni alloy and the formation of a hard Ni2W4C phase, the WC–(Ni, W) cemented carbide exhibited the greatest hardness.